Somatosensory system hyperexcitability in alternating hemiplegia of childhood. (17th July 2014) - Vollono, C.; Rinalduzzi, S.; Miliucci, R.; Vigevano, F.; Valeriani, M.
<x xml:space="preserve">Abstract</x> Background and purpose Alternating hemiplegia of childhood (AHC) is a rare neurological disease characterized by recurrent paroxysmal attacks of hemiplegia. The aim of the study was to assess the recovery cycle of the somatosensory evoked potentials (SEPs) in a group of AHC patients. Methods Seven AHC patients and 10 control age‐matched subjects (CS) were recruited. Right and left median nerve SEPs were recorded. The somatosensory system excitability was assessed by calculating the SEP changes after paired electrical stimuli. All patients were studied during the interictal phase, whilst four patients were studied also during the ictal phase. Results In AHC patients during the interictal phase, the amplitudes of the cervical N13 and of the cortical N20, P24 and N30 responses showed a faster recovery than in CS. In AHC patients during the ictal phase, the cortical N20 recovery cycle was prolonged compared with the interictal phase. Conclusions A shortened SEP recovery cycle in AHC during the interictal phase suggests multilevel somatosensory system hyperexcitability in AHC. A partial recovery of this phenomenon during the ictal phase possibly reflects a functional reset of the somatosensory system. Overall, there is a disinhibition of the somatosensory system in AHC, a functional change of brain function associated with a possible involvement of the Na+/K+ channels. This abnormality and its partial recovery during the attacks might be linked to the pathophysiological and genetic mechanisms of the disease.